Diagnóstico de uso racional da água em prédios do campus I da Universidade de Passo Fundo - RS - Gil, Anelise Sertoli Lopes (2013)
Actions that influence the reduction of water consumption in buildings have been implemented across the board, especially in large urban centers, where water scarcity is a reality, whether by natural causes, the increased demand caused by population growth or both causes. To restore the balance between supply and demand for water, and ensure the sustainability of economic and social development, a new form of behavior should be taken by people changing their habits and developing a culture of rational use of this resource that is vital. It is extremely important to develop studies for the implementation of programs of conservation and rational use of water in buildings, thus leaving simply be an economic issue of financial resources, in the case of a social and environmental responsibility. In this context, this study aimed to diagnose building systems of cold water and assess the feasibility of implementing a water conservation program in three buildings on Campus I, University of Passo Fundo - RS. The methodology was based on conservation programs and water use in structured steps: site characterization, system flow measurements in buildings; audit consumption, primary diagnosis, characterization and diagnosis of building water consumption. The research was conducted in the building of the Institute of Biological Sciences, the building of Pharmacy course and building the speech therapy course with the installation of water meters in each building. With the results in the diagnosis of consumption was observed that the equation applied to calculate the estimated monthly consumption would not be appropriate for the characteristics of the southern region, as cited by Faresin (2006). For the buildings evaluated, could be considered more variables in the equation characterizing better the estimated monthly consumption. However, the possibility of implementing a water conservation program in three buildings of the Campus I, University of Passo Fundo - RS would be possible as the type and condition of the buildings evaluated is satisfactory and suitable for implementation of the program